Redes sociais na internet : a influência da recomendação online na intenção de consumo - Rangel Netto, Nelson Siqueira (2012)
The main goal of this study is to evaluate if online recommendations posted on the social network facebook has an effect on its members intention of consumption and the impact of a variety of mediators, noted reputation of information’s source, recommende